Interindividual variation of NETosis in healthy donors: introduction and application of a refined method for extracellular trap quantification - Hoffmann, Jochen; Schäkel, Knut; Gaiser, Maria; Enk, Alexander; Hadaschik, Eva (Experimental dermatology, 2016)
Neutrophil extracellular trap (NET) formation is a mechanism of innate immune defence by which neutrophil (polymorphonuclear) granulocytes (PMN) produce net-like structures of decondensed chromatin decorated with antimicrobial peptides for trapping and possibly killing microorganisms. If this process leads to cell death, it is termed NETosis. Alterations of this particular mechanism have been reported to be involved in the pathogenesis of chronic inflammatory diseases including psoriasis and lupus erythematosus. Still, quantification of NETosis poses a considerable challenge. We report and test a refined protocol for morphological NET quantification in healthy human donors that encompasses isolation, stimulation, DNA staining, live imaging and semi-automated offline analysis. The results were highly reproducible and in good agreement with manual counting. The average intra-donor coefficient of variation of NETosis rates to phorbol myristate acetate (PMA) stimulation was low compared to the respective interdonor coefficient of variation (10% vs 82%, n=4, respectively, if experiments were repeated on the same day, and 38% vs 74%, n=6, respectively, if experiments were repeated on average 42±34 days apart). Overall, the interdonor coefficient of variation was 67% (n=10). These findings altogether support the existence of a distinct predisposition of PMN from different donors for undergoing NETosis. Picogreen fluorescence correlated stronger to cell death than to morphological NETosis (r2=.89, P<.001, n=8, and r2=.68, P=.012, n=8, respectively). This indicates that cytotoxicity may confound Picogreen fluorescence. Our results and the related protocol may help investigators with the quantification of NETosis and the design of respective basic and translational research studies.